2019
DOI: 10.1186/s12864-019-6373-y
|View full text |Cite
|
Sign up to set email alerts
|

Genomic identification and characterization of MYC family genes in wheat (Triticum aestivum L.)

Abstract: BackgroundMYC transcriptional factors are members of the bHLH (basic helix-loop-helix) superfamily, and play important roles in plant growth and development. Recent studies have revealed that some MYCs are involved in the crosstalk between Jasmonic acid regulatory pathway and light signaling in Arabidopsis, but such kinds of studies are rare in wheat, especially in photo-thermo-sensitive genic male sterile (PTGMS) wheat line.Results27 non-redundant MYC gene copies, which belonged to 11 TaMYC genes, were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…The remaining 63 copies were all fragmental replications, suggesting that fragmental replication was associated with the evolution of the wheat GH9 family and the expansion of members. The findings indicated that fragmental replication may be the main driver of the wheat GH9 gene family expansion, in line with previous research [ 29 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The remaining 63 copies were all fragmental replications, suggesting that fragmental replication was associated with the evolution of the wheat GH9 family and the expansion of members. The findings indicated that fragmental replication may be the main driver of the wheat GH9 gene family expansion, in line with previous research [ 29 ].…”
Section: Resultssupporting
confidence: 91%
“…Hormone-responsive elements are enriched in these TaGH9s , especially MeJA response elements (TGACG-motif and CGTCA-motif) and abscisic acid response elements (ABRE element) are enriched in the TaGH9 family ( Figure 4 ). The latest research has informed us that GA and JA signaling are associated with anther dehiscence in BS366 [ 29 , 37 ]. Phytohormone crosstalk as a massive network has been known to be involved in plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…At the C-terminal of the Dof proteins, there is a transcription regulation domain with diverse functions involving interaction with a variety of regulatory proteins and activating the gene expression 15 . Indeed, previous studies corroborated its functional role in plant growth and development, such as in flowering control 16 , 17 , maturation 18 , seed development 19 , and germination 20 , 21 . Specifically, mutant dag1 (encoding a Dof transcription factor in Arabidopsis) seeds are induced to germinate by much lower red light fluence rates 22 ; the COG1 gene (encoding a Dof protein in Arabidopsis) functions as a negative regulator in phytochrome signaling pathways 23 ; CDFs (CYCLING DOF FACTORS, Dof-type transcriptional repressors) that directly suppresses the expression of CONSTANS ( CO ), which could prevent the expression of photoperiodic gene, the perception of day-length and the floral transition in Arabidopsis 24 .…”
Section: Introductionmentioning
confidence: 59%
“…In order to name all wheat WRKY genes sequentially, we utilized a consistent naming pattern based on their phylogenetic relationships and chromosome locations in A, B, and D subgenomes (Bai et al, 2019). First, each name of the wheat WRKY genes was started with the abbreviation of the species name Triticum aestivum (Ta).…”
Section: Naming Of Wheat Wrky Genesmentioning
confidence: 99%